Strategi Pemberdayaan Masyarakat Berbasis Gerakan Filantropi Islam : Studi Kasus Pada Lazismu Di Kota Medan - Hasim Pratama Daulay; Faisal Riza; Ahmed Fernanda Desky (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research tries to explain the Empowerment Strategy implemented by LAZISMu as a social institution operating in the field of philanthropy. Social inequality and efforts to eradicate it through empowerment programs are the main focus of this research. Relying on many theories and opinions put forward by Charles Tilly, in his theory Tilly said that the emergence of collective movements was due to the reflection of responses to complaints, shortcomings, ambiguity, structural tensions and other social suffering. This research uses qualitative methods and involves a lot of observation processes. The conclusion of this research is that the movement built by LAZISMu is a form of Muhammadiyah's response as a religious organization which sees ignorance and poverty as the main problems hampering this country. Therefore, empowerment is carried out as a strategy and effort to improve social welfare.